4.3: Sense the Threshold Voltage Difference of AMOLED Displays at High‐speed. (26th August 2021) - Dou, Wei; Xu, Jing; Zeng, Yuchao; Hwang, Jason
Abstract : For large‐size AMOLED displays, we usually improve the electrical non‐uniformity of the display through external compensation technology, in order to enhancing the brightness uniformity of the display. The electrical non‐uniformity refers to the threshold voltage (Vth) and mobility distribution of different sub‐pixel driving TFTs in the display. The traditional method of Vth sensing is the source follow method. This method will be affected by the large parasitic capacitance of the sense‐line. So that, we will take a long time to sample the voltage from the sense‐line, and the production efficiency will be decrease. In addition, it is necessary to sense and compensate the display periodically during use, so a longer sensing time will also affect the user experience. In this paper, we propose two methods to detect the Vth difference at high‐speed. The key principle is increasing the drain‐source current (Ids) of different sub‐pixels during sensing. Therefore, charging can be completed quickly to the sense‐line, and we can obtaining the Vth difference of the driving TFT between different sub‐pixels quickly. According to the display effect after compensation, the new detection methods has a big practical application prospect.